Coexistent rheumatoid arthritis and systemic lupus erythematosus: clinical, serological, and phenotypic features. Issue 2 (February 1992) - Brand, C A; Rowley, M J; Tait, B D; Muirden, K D; Whittingham, S F
Abstract : The clinical and serological features and HLA phenotypes are reported for 11 patients with coexistent features of rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). All patients had a symmetrical small joint polyarthritis and features of SLE such as rash, photosensitivity, oral ulceration, serositis, cytopenia, and biopsy proved lupus nephritis. Eight had hypocomplementaemia. Autoantibodies were characteristic of the two diseases: all patients had rheumatoid factor and antibodies to double stranded DNA, eight (73%) had antibodies to collagen, and five (46%) had antibodies to Ro (SS-A). There was also an overlap of HLA phenotypes. Six patients were DR4 and seven were DR2 or DR3 positive, and of the five patients who were DR4 negative, four shared class I alleles often associated with DR4. If RA and SLE share a common autoimmune dysfunction, those patients who have the two diseases do so because they have genetic determinants of both.